Domino-Heck Reactions of Carba- and Oxabicyclic, Unsaturated Dicarboximides: Synthesis of Aryl-Substituted, Bridged Perhydroisoindole Derivatives - Celik, Cumali; Kulu, Irem; Ocal, Nuket; Kaufmann, Dieter E. (WILEY-V C H VERLAG GMBH, 2009)
The C-C coupling of the two bicyclic, unsaturated dicarboximides 5 and 6 with aryl and heteroaryl halides gave, under reductive Heck conditions, the C-aryl-N-phenyl-substituted oxabicyclic imides 7a-c and 8a-c (Scheme3). Domino-Heck C-C coupling reactions of 5, 6, and 1b with aryl or heteroaryl iodides and phenyl- or (trimethylsilyl)acetylene also proved feasible giving 8, 9, and 10a - c, respectively (Scheme 4). Reduction of 1b with LiAlH4 (-> 11) followed by Heck arylation and reduction of 5 with NaBH4 (-> 13) followed by Heck arylation open a new access to the bridged perhydroisoindole derivatives 12a,b and 14a,b with prospective pharmaceutical activity (Schemes 5 and 6).
Keywords: PALLADIUM-CATALYZED REACTIONS; EPIBATIDINE; AMINES; Chemistry